2004
DOI: 10.1186/1471-2202-5-23
|View full text |Cite
|
Sign up to set email alerts
|

Activation of muscarinic acetylcholine receptors elicits pigment granule dispersion in retinal pigment epithelium isolated from bluegill

Abstract: Background: In fish, melanin pigment granules in the retinal pigment epithelium disperse into apical projections as part of the suite of responses the eye makes to bright light conditions. This pigment granule dispersion serves to reduce photobleaching and occurs in response to neurochemicals secreted by the retina. Previous work has shown that acetylcholine may be involved in inducing light-adaptive pigment dispersion. Acetylcholine receptors are of two main types, nicotinic and muscarinic. Muscarinic recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
19
1
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 27 publications
5
19
1
1
Order By: Relevance
“…In the present study we extended earlier pharmacological studies by employing additional subtype-specific antagonists not tested by González et al (2004) for M 1 , M 2 and M 3 receptors. M 5 -selective agents were not available.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…In the present study we extended earlier pharmacological studies by employing additional subtype-specific antagonists not tested by González et al (2004) for M 1 , M 2 and M 3 receptors. M 5 -selective agents were not available.…”
Section: Discussionmentioning
confidence: 83%
“…show carbachol at nanomolar concentrations operates through muscarinic receptors to induce pigment granule dispersion in bluegill RPE. Furthermore, González et al (2004) observed that antagonists specific for M 2 and M 4 receptors failed to block carbachol-induced pigment granule dispersion, and an agonist specific for M 2 receptors failed to induce pigment granule dispersion. In contrast, antagonists specific for M 1 and M 3 receptors blocked carbachol-induced pigment granule dispersion, and an agonist specific for M 1 receptors activated dispersion.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations